Fox Running : a novel - Knudson, R. R. (Rozanne Ruth), 1932-2008.; Koehn, Ilse. (New York : Avon Books, 1981)
A track coach wants a young Indian girl to join his team. She has trouble blending the Indian teachings that are part of her skill with the new coaching.
Keywords: Indians of North America -- Fiction; Running -- Fiction